Road Accident Analysis of Motorcycles Using Geographic Information System. Case Study: Tunja-Boyacá - Pérez-Cantor, Juan Camilo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This research shows the results of applying the technique of using Kernel density variables to develop accident density maps on motorcycles.  Though Geographic Information Systems (GIS) in the city of Tunja, Boyacá, which is listed as an intermediate city according to DANE, in the period corresponding to 2016-2018. In Boyacá, specifically in its capital, Tunja. It is important to implement new measures that are the result of research and so that they can adapt to the geographical, economic, and social characteristics of the studied area in order to mitigate the situation that occurs due to various causes attributed to drivers, mainly motorcyclists, who involve pedestrians and different road users. This analysis contemplates the different road corridors with accident rate in the city of Tunja. It is important to emphasize that the research was carried out under a qualitative and quantitative approach; the information was extracted from databases obtaining the parameters that determine the Kernel density variables through Geographic Information Systems (GIS). The points of view of the actors involved in this case the motorcyclists were evaluated and analyzed. Finally, this research concludes the spatial and temporal analysis to identify the sections of critical incidence in the city, which can be corrected through architectural, engineering and urban interventions to improve, prevent and avoid accidents in the city.